Psalms as Torah : reading biblical song ethically - Wenham, Gordon J. (Grand Rapids, MI : Baker Academic, 2012)
The Psalms are the most-read part of the Old Testament, but their importance for ethics has often been overlooked. However, the Psalms offer some of the most potent ethical instruction in the Bible. In this book internationally renowned Old Testament scholar Gordon Wenham examines the source of the Psalms' power, reflects on their main ethical themes, and shows how they function as prayers that change us. --from publisher description
Jewish and Christian approaches to the Psalms -- Critical approaches to the Psalms -- The Psalter as an anthology to be memorized -- The unique claims of prayed ethics -- The concept of the law in the Psalms -- Laws in the Psalter -- Narrative law in the Psalter -- Virtues and vices in the Psalter -- Appeals for divine intervention -- The ethic of the Psalms and the New Testament.
Includes bibliographical references (p. 209-215) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Ethics in the Bible